SISTEM PENGEMBANGAN KARIR GURU APARATUR SIPIL NEGARA DI KABUPATEN PRINGSEWU - Aswad, Fatqul Hajar (PRIMER : Jurnal Ilmiah Multidisiplin, 2023)
The literature review intend to find out the system being developed by the government of the Republik of Indonesia in developing teacher careers as a from of appreciation fo teacher performance state civil apparatus. The methodd used is in the form of review of regulation governing the management of carrer developmet for functional positions of teachers in the from of low, government regulation and relevand ministry regulation. The results of the literature review can be described that the teacher career development system is an integral part of the teacher reward and protection system. The implementation of teacher career development is implemented in a system called Pengembangan Keprofesian Berkelanjutan (PKB). The system used for evaluating teacher work performance is called the teacher functional credit score system. Suggestions recommended by the results of this literature review include: (1) Appreciation for teachers should not only be manifested in career development, however, increasing the welfare and protection of the profession deserves serious attention from the central and regional governments (2) The application of the credit score system for functional teacher positions must be done transparently, accountable, and using a Digital-Based Information System to be effective and efficient.